8
$\begingroup$

I try to find a partial fraction expansion of $\dfrac{1}{\prod_{k=0}^n (x+k)}$ (to calculate its integral). After checking some values of $n$, I noticed that it seems to be true that $\dfrac{n!}{\prod_{k=0}^n (x+k)}=\sum_{k=0}^n\dfrac{(-1)^k{n \choose k}}{x+k}$. However, I can't think of a way to prove it. Can somebody please help me?

$\endgroup$
14
$\begingroup$

Since every $k,\; k=-n,\ldots, 0$ is a simple pole of the given fraction then its decomposition take the form

$$\frac{1}{x(x+1)(x+2)...(x+n)}=\sum_{k=0}^n\frac{a_k}{x+k}$$ and we have $$a_k=\lim_{x \to -k}\sum_{i=0}^n\frac{a_i(x+k)}{x+i} = \lim_{x \to -k} (x+k)\sum_{i=0}^n\frac{a_i}{x+i}$$ $$= \lim_{x \to -k} \frac{x+k}{x(x+1)(x+2)...(x+n)}=\frac{1}{-k(-k+1)(-k+2)...(-k+n)}=\frac{(-1)^k}{k!(n-k)!}$$ so yes it's true that $$\frac{n!}{x(x+1)(x+2)...(x+n)}=\sum_{k=0}^n\frac{(-1)^k{n\choose k}}{x+k}$$

$\endgroup$
  • $\begingroup$ Well done, my friend! $\endgroup$ – Namaste Mar 18 '14 at 12:20
12
$\begingroup$

Notice that: $$ \frac{1}{x(x+1)\cdots(x+n)} = \frac{1}{n} \frac{(x+n) - x}{x(x+1)\cdots(x+n)} = \frac{1}{n} \left(\frac{1}{x(x+1)\cdots(x+n-1)} - \frac{1}{(x+1)\cdots(x+n)}\right) $$

This gives you a recursion formula for partial fraction expansion. You can use it to check your conjecture, and prove it by induction if it's indeed true.

See also this answer: Series of inverses of binomial coefficients for another approach.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.